A Guide to Language Courses: School of Languages, Literacies and Translation, Academic Session 2017/2018 - PBT, Pusat Bahasa & Terjemahan (Pusat Pengajian Bahasa Literasi & Terjemahan, 2017)
http://www.imcc.usm.my/images/academichandbook/A-Guide-To-Language-Courses---BI.pdf